The factors determinating a physical state and inflating the evaluation of the nursing care - Szutarska, Aleksandra; Andruszkiewicz, Anna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2010)
The main aim of the research is to present the psychical components, which influence the nursing evaluation. The psychical dimension of the illness was stressed, as the dimension of individual experience which link cognitive element with emotional element. There were also presented varieties of the life situations determining the way of illness experiencing and attitude towards it. In the psychical dimension there were presented the defense mechanisms activated by a patient as well as the significance of the occurring stress. The implications of biological stress influencing the homeostasis disorder of the organism which can release many psychosomatic diseases. In the quality criterion of the nursing care concerning the service, what is important is the emotional state in the form of satisfaction or its absence. Professional nursing in accordance with professional ethics principles as well as the holistic approach to the process of nursing by nurses allows to fulfill this criterion.